1994
DOI: 10.1111/j.1469-8137.1994.tb02953.x
|View full text |Cite
|
Sign up to set email alerts
|

Stay‐green genotypes of Phaseolus vulgaris L.: chloroplast proteins and chlorophyll catabolites during foliar senescence

Abstract: SUMMARYLeaf senescetYce was analyzed in stay-green mutants of Phaseolus vulgaris. Impaired yellowing in these genotypes was accompanied by abnormal retention of tbylakoid membrane proteins including tbe ligbt-bar\'esting cblorophyll-binding protein of photosystem II, tbe 33 kDa polypeptide of tbe oxygen-evolving complex, cytocbrome/ and tbe psaF protein of pbotosystem I. On tbe other band, ribulose bispbospbate carboxylase was somewbat more labile in tbe mutant than tbe wild-type. Tbe stay-green cbaracter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…In addition, the proteomic analysis identified rbcL as one of the major proteins with lower abundance in nan (Figs. 5 and 6; Table V), which differs from the results seen with a rice sgr mutant and the retention of Rubisco in leaves of the tomato green flesh mutant (Akhtar et al, 1999) but agrees with the previously observed reduced Rubisco protein levels in a P. vulgaris stay-green mutant (Bachmann et al, 1994). If photosynthetic capacity is insufficient under conditions of excess absorbed light, free Chl can generate ROS, which in turn can cause extensive oxidative damage to the thylakoid membrane (Barber and Andersson, 1992;Niyogi, 1999).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the proteomic analysis identified rbcL as one of the major proteins with lower abundance in nan (Figs. 5 and 6; Table V), which differs from the results seen with a rice sgr mutant and the retention of Rubisco in leaves of the tomato green flesh mutant (Akhtar et al, 1999) but agrees with the previously observed reduced Rubisco protein levels in a P. vulgaris stay-green mutant (Bachmann et al, 1994). If photosynthetic capacity is insufficient under conditions of excess absorbed light, free Chl can generate ROS, which in turn can cause extensive oxidative damage to the thylakoid membrane (Barber and Andersson, 1992;Niyogi, 1999).…”
Section: Discussionsupporting
confidence: 84%
“…Those identified to date span a broad taxonomic range, including members of the Gramineae (durum wheat [Triticum durum; Spano et al, 2003]; Festuca pratensis [Thomas, 1987]; rice [Oryza sativa; Cha et al, 2002;Jiang et al, 2007;Kusaba et al, 2007;Park et al, 2007]), Arabidopsis (Arabidopsis thaliana; Woo et al, 2001;Oh et al, 2003Oh et al, , 2004Ren et al, 2007), and the Leguminosae (soybean [Glycine max;Guiamét andGiannibelli, 1994, 1996;Luquez and Guiamét, 2002]; Phaseolus vulgaris [Ronning et al, 1991;Bachmann et al, 1994]; pea [Pisum sativum; Armstead et al, 2007;Sato et al, 2007]). A stay-green mutant phenotype has also been reported in tomato (Solanum lycopersicum) fruits (the green flesh mutant; Cheung et al, 1993;Akhtar et al, 1999) and pepper (Capsicum annuum; mutant chlorophyll retainer; Efrati et al, 2005;Roca and Mínguez-Mosquera, 2006).…”
mentioning
confidence: 99%
“…3A, B). LHCII was fully retained during the course of senescence in JI2775, a feature that has been described in different stay-green mutants (Hilditch et al, 1989;Bachmann et al, 1994;Pružinská et al, 2003;Park et al, 2007), but in contrast to the stay-green mutant Bf993 of Festuca pratensis (Thomas and Howarth, 2000), proteolytic fragments of LHCII could not be detected in JI2775. In addition, core subunits of PSI (PsaD) and PSII (PsbA) were also retained to some extend in the mutant, and degradation of Rubisco subunits was somewhat slower in JI2775 compared to JI4.…”
Section: Resultsmentioning
confidence: 70%
“…1), which accumulate in the vacuoles of senescent leaves (5,6,15). Under conditions where senescenceinduced Chl breakdown occurred with high rates, FCCs were observed temporarily and suggested to be catabolic intermediates preceding the NCCs (29,30).…”
Section: Discussionmentioning
confidence: 99%